CULTURAL DIFFERENCES IN ENGLISH AND RUSSIAN LEXICAL EXPRESSIONS OF VALUATION - Husniddin qizi, Pardaeva Farangiza (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study attempts to analyze the differences in lexical, idiomatic and pragmatic forms of valuation used in English and Russian, pointing out cultural patterns, conventional ways to speak and meaning. Method: By taking a cross-linguistic, data-driven approach, this research explains how we value objects on various cultural and pragmatic levels, filling in gaps noted in earlier research and practice. Results: It was found that English often chose language that is soft and polite, but Russian prefers straightforward, emotionally expressive language focusing on being sincere and clear in its values, illustrating how their cultures differ. Novelty: Despite the previous research available on metaphor and universals, not many have studied and compared the evaluative lexical units from these two languages using an integrated method. Unique Point: Although English and Russian agree that value is commonly matched to height or brightness in thought, English generally considers it within a personal and financial context, whereas Russian prefers talking about value in terms of morality, community and emotions.